Breakdown voltage investigation of fusion SiO2 optical coupler switch using Pockel effect model - Saktioto; Hanim, Nor Faridah; Phing, Ho Sze; Fadhali, Mohamed; Yupapin, Preecha; Ali, Jalil (My University, 2009)
This paper describes a new model for the breakdown voltage of SiO 2 fiber coupler using the Pockel effect and empirical equation. The model is evaluated by using the coupling coefficient and the changes in the refractive index. We found that the breakdown voltage is in the order of 10 2 volt correspond to coupling coefficient by the order of mm -1. Increasing the value of coupling coefficient between the electrodes leads to a reduction in the breakdown voltage. © 2009 SPIE.
Keywords: Empirical equation; Optical switch; Pockel effect; Single mode fiber